Sam Ratulangi's philosophical cultural ideas and their implications in the principle of just and civilized humanity - Pangalila, Theodorus; Loho, Ambrosius Markus; Tanase, Tasente (Universitas Negeri Yogyakarta, 2022)
The article aims to explore the philosophical thinking of Si Tou Timou Tumou Tou (living human to humanize others) concerning the noble values contained in the second principle of the Pancasila,